Molecular and Mechanical Mechanisms of Calcification Pathology Induced by Bicuspid Aortic Valve Abnormalities - Kazik, Hail B.; Kandail, Harkamaljot S.; LaDisa, John F.; Lincoln, Joy (Frontiers in Cardiovascular Medicine, 2021)
Bicuspid aortic valve (BAV) is a congenital defect affecting 1-2% of the general population that is distinguished from the normal tricuspid aortic valve (TAV) by the existence of two, rather than three, functional leaflets (or cusps). BAV presents in different morphologic phenotypes based on the configuration of cusp fusion. The most common phenotypes are Type 1 (containing one raphe), where fusion between right coronary and left coronary cusps (BAV R/L) is the most common configuration followed by fusion between right coronary and non-coronary cusps (BAV R/NC). While anatomically different, BAV R/L and BAV R/NC configurations are both associated with abnormal hemodynamic and biomechanical environments. The natural history of BAV has shown that it is not necessarily the primary structural malformation that enforces the need for treatment in young adults, but the secondary onset of premature calcification in approximately 50% of BAV patients, that can lead to aortic stenosis. While an underlying genetic basis is a major pathogenic contributor of the structural malformation, recent studies have implemented computational models, cardiac imaging studies, and bench-top methods to reveal BAV-associated hemodynamic and biomechanical alterations that likely contribute to secondary complications. Contributions to the field, however, lack support for a direct link between the external valvular environment and calcific aortic valve disease in the setting of BAV R/L and R/NC BAV. Here we review the literature of BAV hemodynamics and biomechanics and discuss its previously proposed contribution to calcification. We also offer means to improve upon previous studies in order to further characterize BAV and its secondary complications.